Influence of zirconium dioxide (ZrO2) and magnetite (Fe3O4) additions on the structural, electrical, and biological properties of Bioglass® for metal implant coatings - Hammami, Imen; Fernandes Graça, Manuel Pedro; Gavinho, Sílvia Rodrigues; Regadas, Joana Soares; Jakka, Suresh Kumar; Pádua, Ana Sofia; Silva, Jorge Carvalho; Sá-Nogueira, Isabel; Borges, João Paulo (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundThe growing need for durable implants, driven by aging populations and increased trauma cases, highlights challenges such as limited osseointegration and biofilm formation. 45S5 Bioglass® has shown promise due to its bioactivity, antimicrobial properties, and ability to enhance osseointegration through electrical polarization. This study investigates the effects of incorporating different concentrations of ZrO2 and Fe3O4 into 45S5 Bioglass® to enhance its electrical and biological properties.MethodsRaman analysis was used to evaluate how these oxides influenced the amount of non-bridging oxygens (NBOs) and glass network connectivity. Electrical characterization was performed using impedance spectroscopy to measure conductivity and ion mobility. Antibacterial activity was assessed using the agar diffusion method, and bioactivity was evaluated through simulated body fluid (SBF) immersion tests.ResultsThe results revealed that bioglasses containing ZrO2 exhibited higher NBO content compared to Fe3O4, leading to improved electrical and biological properties. ZrO2, particularly at 2 mol%, significantly enhanced conductivity, antibacterial activity, and bioactivity. In contrast, Fe3O4 reduced both antibacterial activity and bioactivity.ConclusionThe findings demonstrate that ZrO2 addition improves the electrical and biological performance of 45S5 Bioglass®, making it a promising candidate for durable implants. Fe3O4, however, showed limited benefits.